(3TQM GdCNVQj Ydi GdSde GdeQhfbs - (3GdCNVQj, YHO GdQMef Hf eMeO Hf eMeO J (B983 (3g`s
(3ChdgG (B:s
.. (3hEf cfJ dSJ CgdG dPdc hdcf Medfj Ydjg JaGDdj (B.. (3GdMeO ddg GdPj bO CNQL fJGFL GdacQ dCQHGH GdMLG ; bGd GdeMbbhf GdMeO gh GdKfGA HGdcdGe Ydi GdeMehO HLejd UaGJg eWdbG Cj ShGA cGfJ ef HGH GdEMSGf Ch (B...s
(3BNQgG (B:s
... (3bO JbOe GdcdGe aj GdNWHI Ydi eG jJYdb HGdUdGI Ydjg Udi Gddg Ydjg hSde hbhdfG eG bWYJ GdHjJ eG eUOQjI XQajI hdaX CHQL LeY bdI hGdeQGO GdcKQI dGfgG GKfJG YTQ HQLG (B... (3aSHMGf Gddg (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\331s
(3GdCYdGe (B3\331s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs